If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 4x = 36 + 3 Combine like terms: 36 + 3 = 39 3 + 4x = 39 Solving 3 + 4x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4x = 39 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = 39 + -3 4x = 39 + -3 Combine like terms: 39 + -3 = 36 4x = 36 Divide each side by '4'. x = 9 Simplifying x = 9
| X-(2x+1)=3-2(x+3) | | 12x-26=0x+4 | | x/12=-15 | | 69=-3(8a+1) | | -4(3x-1)=-20 | | 6x+4y+8z-4x+5z-7y= | | 6-8(1-7x)=-2-4x | | -4(3x-1)=-10 | | -1=5v+7-v | | -1=5v+7-v | | 11/23+11/23 | | 2x^3-9x^2+12x-4=0 | | 8/14-7/14 | | -139-9x=10x+21 | | -129-10x=132-31x | | -129-10x=132-31x | | 2y^2+26y+24=0 | | z^3-0.5*z+0.25=0 | | 85-5x=57-2 | | 0.2x+1.6=2 | | 12w^2+7w-10=0 | | 8/12*30/40 | | 46.00=4.00*m+2.00 | | 1.5(-4)+7.5= | | m*5+4=7 | | 4-(a+3)-13= | | 2(3x-1)-(4+2x)=5+x | | 5x+8=8x-17 | | x^3-60x^2+1200x-8000=0 | | 4x+35=11x+4 | | 2+2=22 | | 2+(3-b)*3-11b= |